2021
DOI: 10.1108/nfs-07-2021-0201
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and dietary intake in young university students in the UK

Abstract: Purpose Vitamin D deficiency is prevalent worldwide. This paper aims to investigate the vitamin D status and dietary intake in young university students. Design/methodology/approach Forty-one healthy students aged 18–29 years from Coventry University UK were recruited during January-February 2019, including white Caucasians (n = 18), African-Caribbeans (n = 14) and Asians (n = 9). Plasma 25(OH)D concentrations were measured and dietary vitamin D intake was determined. Chi-square and simple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Also, persons in the fourth quartile for MPF pattern scores had higher BMI compared with those in the first quartile. Several studies showed that body adiposity is inversely related to serum vitamin D (58,59) . This is mainly due to the sequestration of vitamin D by the adipose tissue (60) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, persons in the fourth quartile for MPF pattern scores had higher BMI compared with those in the first quartile. Several studies showed that body adiposity is inversely related to serum vitamin D (58,59) . This is mainly due to the sequestration of vitamin D by the adipose tissue (60) .…”
Section: Discussionmentioning
confidence: 99%
“…A diet poor in vitamin D is another risk factor that may contribute to its low levels. A study from the UK found that students do not get enough vitamin D through their diet, where only 14% of respondents met recommended intake levels (30). A similar trend was noticed among students in China (31).…”
Section: Circumstances That May Have Affected Vitamin D Levelsmentioning
confidence: 79%
“…Hypovitaminosis D prevalence varied by region: 44–96% in the Middle East and North Africa [ 14 ], 30–60% in Europe [ 15 ], and ~24% in the US [ 16 ]. Among several factors, dark skin tone [ 17 ] and adiposity [ 18 ] were directly related to the prevalence of vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%